2015
DOI: 10.1016/s0140-6736(15)61120-5
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab and teriparatide transitions in postmenopausal osteoporosis (the DATA-Switch study): extension of a randomised controlled trial

Abstract: BACKGROUND Unlike most chronic diseases, approved osteoporosis treatments are generally limited to a single drug at a fixed dose and frequency. Nonetheless, no approved therapy is able to restore skeletal integrity in most osteoporotic patients and the long-term use of most osteoporosis drugs remains controversial due to efficacy and safety concerns. Thus, many patients are treated with the sequential use of two or more therapies. Discontinuing teriparatide and denosumab, two of our most potent agents, results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
307
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 450 publications
(341 citation statements)
references
References 37 publications
7
307
0
14
Order By: Relevance
“…(38) It is not clear that switching treatment will offer additional reduction in risk of nonvertebral fracture. (4,(39)(40)(41)(42)(43)(44) Based on studies from patients who are not receiving treatment, the increase in risk of fracture associated with an incident nonvertebral fracture may be greatest in the first 5 years after the fracture occurs and then wane with time. (24)(25)(26)(27)(28)(29)(30)(31) Furthermore, in patients receiving zoledronic acid, incident nonvertebral fracture is an important risk factor for future nonvertebral fractures over the next 3 years if therapy is discontinued.…”
Section: Monitoring Response To Therapymentioning
confidence: 99%
“…(38) It is not clear that switching treatment will offer additional reduction in risk of nonvertebral fracture. (4,(39)(40)(41)(42)(43)(44) Based on studies from patients who are not receiving treatment, the increase in risk of fracture associated with an incident nonvertebral fracture may be greatest in the first 5 years after the fracture occurs and then wane with time. (24)(25)(26)(27)(28)(29)(30)(31) Furthermore, in patients receiving zoledronic acid, incident nonvertebral fracture is an important risk factor for future nonvertebral fractures over the next 3 years if therapy is discontinued.…”
Section: Monitoring Response To Therapymentioning
confidence: 99%
“…Additionally, it is very clear that switching from denosumab to the anabolic agent teriparatide, and presumably abaloparatide as well, should be avoided because this transition is associated with even more extensive skeletal remodeling and even greater bone loss than that observed when denosumab is discontinued without a drug transition. (14) Finally, although not addressing the issue directly, this report raises questions concerning the optimal timing of bisphosphonate administration when used after denosumab. Given bisphosphonates' mechanism of action and preferential deposition at sites of active bone remodeling, (15) it is plausible that if exposure occurs while denosumab's antiresorptive effects are still maximal, the drug will be considerably less effective than if given to a patient with ongoing robust bone turnover.…”
mentioning
confidence: 93%
“…(18)(19)(20)(21)(22)(23) This is certainly true of TPTD and PTH. (24)(25)(26)(27)(28)(29)(30) BMD responses to initial TPTD/PTH followed by potent antiresorptive therapy are substantial in both spine and hip sites as a result of the effects of both components of the treatment sequence. (28,(31)(32)(33)(34) In contrast, several studies have indicated that hip BMD responses to TPTD are lower in patients who have already been pretreated with potent antiresorptive therapies and consistently decline transiently for the first year or even longer.…”
Section: Introductionmentioning
confidence: 99%
“…(24)(25)(26)(27)(28)(29)(30) BMD responses to initial TPTD/PTH followed by potent antiresorptive therapy are substantial in both spine and hip sites as a result of the effects of both components of the treatment sequence. (28,(31)(32)(33)(34) In contrast, several studies have indicated that hip BMD responses to TPTD are lower in patients who have already been pretreated with potent antiresorptive therapies and consistently decline transiently for the first year or even longer. (24)(25)(26)(27)(28)30) Although there are no fracture endpoint trials in these antiresorptive pretreated patients, the substantial differences in BMD outcome, particularly for the hip region, suggest that TPTD effects against fracture could also differ in these pretreated patients.…”
Section: Introductionmentioning
confidence: 99%